Affordances, Affect and Audiences - Making sense of networked publics, introduction to AoIR 2017 special issue on Networked Publics - Tiidenberg, Katrin; Siibak, Andra (Studies of Transition States and Societies, 2017)
The 2017 annual conference of the Association of Internet Researchers took place in Tartu, Estonia, and was focused on networked publics, which, as the call for papers highlighted, “play an important role in shaping the political, social, economic, cultural but also moral, ethical and value-laden landscapes of contemporary life.” This special issue is comprised of papers presented at the conference (AoIR 2017) and its doctoral colloquium, and engages with the affordances that networked communication technologies (social media platforms, websites, internet based governmental or corporate infrastructures for voting or banking) have for the emergence or maintenance of networked publics; but also, and more specifically, the affordances that these networked publics  have for manifestations of human affect, sociality and sociability. Our collaborators undertake analyses of networked publics of solidarity and hate (Nikunen, this issue; Kuo, this issue), connection and disconnection (Dremljuga, this issue), democratic participation and authoritarianism, tolerance and intolerance (Sikk, this issue; Kuo, this issue), as well as the affordances of networked publics for reaching one’s imagined audiences (Tikerperi, this issue) and whether these imagined audiences evoke individual and institutional trust (Männiste & Masso, this issue).